A TOPCon battery front film layer with anti-UV attenuation effect and preparation method thereof

By designing a stacked alumina film layer and silicon oxynitride film, and combining the matching of the overall temperature increase amplitude, the problem of performance attenuation of TOPCon batteries under ultraviolet irradiation is solved, achieving a significant reduction in UV attenuation effect and extending battery life.

CN118571957BActive Publication Date: 2025-03-11中润新能源(徐州)有限公司

Patent Information

Application Number
CN202410612812.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-17
Publication Date
2025-03-11
Estimated Expiration
2044-05-17

AI Technical Summary

Technical Problem

TOPCon batteries gradually decay under ultraviolet irradiation, resulting in reduced power generation efficiency and aging of materials. The existing technology is difficult to effectively solve this problem.

Method used

By designing a stacked alumina film layer structure, including upper and lower alumina film layers and silicon oxynitride thin films, the battery's anti-UV attenuation effect is enhanced by matching the overall temperature increase amplitude.

Benefits of technology

This film layer structure effectively reduces the interfacial density of alumina, protects the passivation film layer, and improves the barrier ability to H ions, significantly reduces the UV attenuation effect of TOPCon batteries, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118571957B_ABST
    Figure CN118571957B_ABST
Patent Text Reader

Abstract

The invention discloses a TOPCon battery front film layer with anti-UV attenuation effect and a preparation method thereof, belonging to the technical field of battery preparation. The invention adopts atomic layer deposition technology (ALD) and H2O as a precursor source to react in two stages to obtain a laminated aluminum oxide film layer with decreasing OH group content; then a silicon oxynitride film is added on the front laminated aluminum oxide film layer, and then a passivation film layer such as silicon nitride and silicon oxynitride is grown; the laminated structure can greatly reduce the interface state density of aluminum oxide and protect the passivation film layer; at the same time, the silicon oxynitride film layer and the heating process are added, so as to improve the film layer's blocking ability to H ions after UV irradiation, promote the crystallization of the aluminum oxide film layer, increase its effective thickness, and further improve its chemical passivation and field passivation effects, thereby reducing the UV attenuation effect of the TOPCon battery, improving the reliability measures of anti-UV attenuation, and compensating for the high efficiency loss of a single process of increasing the ALD reaction cycle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery preparation, and in particular relates to a TOPCon battery front film layer with anti-UV attenuation effect and a preparation method thereof. Background Art

[0002] Ultraviolet aging degradation (UV degradation) refers to the phenomenon that the performance of solar cell modules gradually deteriorates under long-term exposure to ultraviolet rays. Researchers from the National Accelerator Laboratory (SLAC) and the National Renewable Energy Laboratory (NREL) found that after artificial accelerated ultraviolet irradiation testing, the front power loss of N-type cells was more obvious, which had an adverse effect on the output efficiency of photovoltaic power stations. It has now become an important issue in the application of components in the industry.

[0003] The impact of UV attenuation on photovoltaic cells is mainly reflected in the following aspects: UV attenuation will cause a part of high-energy light energy to be unable to be used by photovoltaic cells, thereby reducing its power generation efficiency; UV band light has high energy, which will cause physical and chemical reactions inside photovoltaic cells, and the photothermal effect will generate too much heat, causing the battery temperature to rise, thereby causing aging and damage to battery materials; UV band light will also cause oxidation reactions of battery materials, leading to corrosion and damage to the battery. Regarding the UV failure mechanism, the industry currently has the following main analyses: 1. Si passivation damage, due to ultraviolet light from the silicon conduction band light injection of electrons into silicon dioxide, resulting in an increase in the recombination center of the Si / SiO2 interface, which destroys the surface passivation by changing the fixed charge density and increasing the interface defect density near the Si surface; 2. Hot carriers destroy the passivation layer, and high-energy photons (i.e. ultraviolet radiation) can generate hot electrons when they excite an electron from the valence band beyond the conduction band. Its mobility and energy are high enough to exceed the interface barrier and be injected into the interface, thereby destroying the passivation layer and increasing the interface state density; 3. Chemical passivation loss. After UV irradiation, the Si-H bonds at the interface are destroyed, hydrogen is redistributed, and the broken bonds of hydrogen on the surface lead to excess H atomic groups, which promotes the recombination of carriers.

[0004] Regarding how to reduce the UV attenuation of TOPCon cells, the current research is only in the preliminary stage. Usually, single measures such as increasing the ALD reaction cycle to increase the thickness of aluminum oxide and the refractive index of the silicon nitride film are adopted, but this will inevitably lead to efficiency losses such as hydrogen passivation loss, reduced effective minority carrier lifetime, and photocurrent loss. Therefore, how to effectively improve the UV attenuation effect of TOPCon cells has become an important challenge that limits the service life of advanced N-type TOPCon cell products and needs to be solved urgently.

[0005] Therefore, in view of the above technical problems, it is necessary to provide a TOPCon battery front film layer with anti-UV attenuation effect and a preparation method.

[0006] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention

[0007] The purpose of the present invention is to provide a TOPCon battery front film layer with anti-UV attenuation effect and a preparation method, which can enhance the anti-UV attenuation effect of the TOPon battery and make up for the efficiency loss caused by the existing single improvement measures by matching the three variables of the thickness of the laminated aluminum oxide, the thickness of the newly added silicon oxynitride film, and the overall temperature rise amplitude.

[0008] In order to achieve the above object, a specific embodiment of the present invention provides a TOPCon battery front film layer with anti-UV attenuation effect, wherein the front film layer structure comprises, from bottom to top, a laminated aluminum oxide film layer, a silicon oxynitride film grown on the laminated aluminum oxide film layer, and a passivation film layer;

[0009] The stacked aluminum oxide film layer comprises an upper aluminum oxide film layer and a lower aluminum oxide film layer, and the -OH group content decreases from the lower aluminum oxide film layer to the upper aluminum oxide film layer.

[0010] The stacked structure can greatly reduce the interface state density of aluminum oxide and protect the passivation film layer; at the same time, the addition of the silicon oxynitride film layer improves the film's ability to block H ions after UV irradiation, promotes the crystallization of the aluminum oxide film layer, and increases its effective thickness, thereby improving its chemical passivation and field passivation effects, thereby reducing the UV attenuation effect of the TOPCon battery, improving the reliability measures against UV attenuation, and compensating for the high efficiency loss of a single process of increasing the ALD reaction cycle.

[0011] In one or more embodiments of the present invention, the total thickness of the laminated aluminum oxide film layer is 4.5±1.5 nm.

[0012] In one or more embodiments of the present invention, the passivation film layer structure is, from bottom to top, a third silicon nitride layer, a second silicon nitride layer, a first silicon nitride layer, a second silicon oxynitride layer, a first silicon oxynitride layer, and a silicon oxide layer.

[0013] A specific embodiment of the present invention also provides a method for preparing a TOPCon battery front film layer with anti-UV attenuation effect, comprising the following steps:

[0014] S1. Determine the total number of atomic layer deposition cycles and divide it into two parts: lower layer / upper layer, and the number of cycles of the lower layer is higher than that of the upper layer;

[0015] S2. Based on the number of reaction cycles in S1, the content of the aqueous phase precursor source in the lower aluminum oxide film layer is ensured to be higher than that in the upper aluminum oxide film layer, different atomic layer deposition chamber reaction temperatures are set, and a stacked aluminum oxide film layer with a decreasing -OH group content is obtained by atomic layer deposition;

[0016] S3, based on the total number of cycles in S1, determining whether the total number of cycles is high or low, and growing a high-thickness or low-thickness silicon oxynitride film according to the total number of cycles;

[0017] S4. Based on S3, a passivation film layer is grown by matching the temperature rise amplitude with a low total number of cycles and a high thickness silicon oxynitride film or a high total number of cycles and a low thickness silicon oxynitride film.

[0018] In one or more embodiments of the present invention, the water-phase precursor in S2 is introduced for 4-10 seconds at a flow rate of 2500-3500 sccm.

[0019] In one or more embodiments of the present invention, in S2, during the preparation of the laminated aluminum oxide film, TMA is introduced using N2 as a source with a flow rate of 2000-4000sccm and an introduction time of 6-8s.

[0020] In one or more embodiments of the present invention, in S2, the reaction temperature of the atomic layer deposition chamber is 240-260°C when preparing the lower aluminum oxide film layer, and the reaction temperature of the atomic layer deposition chamber is 265-275°C when preparing the upper aluminum oxide film layer.

[0021] In one or more embodiments of the present invention, the total thickness of the laminated aluminum oxide film obtained in S2 is 4.5±1.5 nm, and the high and low cycle numbers are divided according to the measured thickness as follows:

[0022] 2.5nm≤low cycle number<3.5nm, 3.5nm≤medium cycle number<4.5nm, 4.5nm≤high cycle number.

[0023] In one or more embodiments of the present invention, in S3, the process time for growing the silicon oxynitride film is 30-70 seconds.

[0024] In one or more embodiments of the present invention, the temperature increase range in S4 is 10-30°C, and the total temperature range after the temperature increase is 460-540°C.

[0025] The beneficial effects of the present invention compared to the prior art are as follows: the present invention takes into account the particularity of UV attenuation of N-type TOPCon batteries, improves the suitable laminated aluminum oxide film layer, avoids the defects of a single improvement method, and unifies the adaptation standards of the three variables of laminated aluminum oxide, newly added silicon oxynitride film, and overall temperature rise of the passivation film layer. The film layer structure design method can be adapted to actual usage conditions, and while improving the anti-UV attenuation effect, it can also ensure the high efficiency of the battery cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0027] Figure 1 This is a schematic diagram of a front film structure of a TOPCon battery with anti-UV attenuation effect in one embodiment of the present invention;

[0028] Figure 2 The present invention is a flowchart of a method for preparing a TOPCon battery front film layer with anti-UV attenuation effect in one embodiment of the present invention.

[0029] Description of main reference numerals:

[0030] 1. TOPCon battery body; 2. Laminated aluminum oxide film layer; 201. Lower aluminum oxide film layer; 202. Upper aluminum oxide film layer; 3. Silicon oxynitride film; 4. Third silicon nitride layer; 5. Second silicon nitride layer; 6. First silicon nitride layer; 7. Second silicon oxynitride layer; 8. First silicon oxynitride layer; 9. Silicon oxide layer. DETAILED DESCRIPTION

[0031] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0032] like Figure 1As shown, a TOPCon battery front film layer with anti-UV attenuation effect in one embodiment of the present invention, the front film layer is located on the surface of the TOPCon battery body 1, and the front film layer structure is, from bottom to top, a laminated aluminum oxide film layer 2, a silicon oxynitride film 3 grown on the laminated aluminum oxide film layer 2, a third silicon nitride layer 4, a second silicon nitride layer 5, a first silicon nitride layer 6, a second silicon oxynitride layer 7, a first silicon oxynitride layer 8, and a silicon oxide layer 9.

[0033] The laminated aluminum oxide film layer 2 includes an upper aluminum oxide film layer 202 and a lower aluminum oxide film layer 201 , and the content of -OH groups decreases from the lower aluminum oxide film layer 201 to the upper aluminum oxide film layer 202 .

[0034] Preferably, the total thickness of the laminated aluminum oxide film layer 2 is 4.5±1.5 nm.

[0035] like Figure 2 As shown, a method for preparing a TOPCon battery front film layer with anti-UV attenuation effect includes the following steps:

[0036] S1. Determine the total number of atomic layer deposition cycles, and divide it into two parts: lower layer and upper layer, and the number of cycles of the lower layer is higher than that of the upper layer (for example, the total number of cycles is 30, which can be divided into two parts: 18 and 12).

[0037] S2. Based on the number of reaction cycles in S1, ensure that the content of aqueous precursor source in the lower aluminum oxide film layer 201 is higher than that in the upper aluminum oxide film layer 202, set different atomic layer deposition chamber reaction temperatures, and use atomic layer deposition to obtain a laminated aluminum oxide film layer 2 with decreasing -OH group content.

[0038] S3, based on the total number of cycles in S1, determining whether the total number of cycles is high or low, and growing a high-thickness or low-thickness silicon oxynitride film 3 according to the total number of cycles;

[0039] When the total number of cycles is relatively low, the silicon oxynitride film 3 with high thickness is grown; when the total number of cycles is relatively high, the silicon oxynitride film 3 with low thickness is grown.

[0040] S4, based on S3, the temperature rise range is matched according to a low total number of cycles with a high thickness silicon oxynitride film 3 or a high total number of cycles with a low thickness silicon oxynitride film 3 to grow a passivation film layer;

[0041] Among them, when a low total cycle number is matched with a thick silicon oxynitride film 3, a large temperature rise amplitude is matched to grow passivation film layers such as silicon nitride and silicon oxynitride. When a high total cycle number is matched with a thin silicon oxynitride film 3, a small temperature rise amplitude is matched to grow passivation film layers such as silicon nitride and silicon oxynitride.

[0042] Preferably, the water phase precursor in S2 is introduced for 4-10s, with a flow rate of 2500-3500sccm; during the preparation of the laminated aluminum oxide film 2, TMA is introduced using N2 source, with a flow rate of 2000-4000sccm and an introduction time of 6-8s; when preparing the lower aluminum oxide film 201, the atomic layer deposition chamber reaction temperature is 240-260°C, and when preparing the upper aluminum oxide film 202, the atomic layer deposition chamber reaction temperature is 265-275°C. The total thickness of the obtained laminated aluminum oxide film is 4.5±1.5nm, and the high and low cycle numbers are divided according to the measured thickness as follows:

[0043] 2.5nm≤low cycle number<3.5nm, 3.5nm≤medium cycle number<4.5nm, 4.5nm≤high cycle number.

[0044] Preferably, in S3, the process time for growing the silicon oxynitride film 3 is 30-70 seconds.

[0045] Preferably, the temperature increase range in S4 is 10-30°C, and the total temperature range after the temperature increase is 460-540°C.

[0046] Specifically, the TOPCon cell that has been put into normal production line and completed all previous processes now needs to prepare the front film structure. The steps are as follows:

[0047] S1, the total number of atomic layer deposition cycles is 28, which is divided into two parts: 16 cycles for the lower layer and 12 cycles for the upper layer;

[0048] S2, the lower layer water phase precursor is introduced for 6s, the flow rate is 3000sccm, the reaction temperature of the atomic layer deposition chamber is 250°C, the upper layer water phase precursor is introduced for 4s, the flow rate is 2500sccm, and the reaction temperature of the atomic layer deposition chamber is 275°C. The TMA introduction time is 7s, the N2 source flow rate is 3000sccm, and the other parameters are obtained after the normal process to obtain the laminated aluminum oxide film layer 2;

[0049] S3. The actual thickness of the laminated aluminum oxide film 2 is tested by laser ellipsometer, and the average value is 3.64nm, which is in line with the range of 3.5nm≤medium cycle number<4.5nm. The process time of adding the new silicon oxynitride film 3 is determined to be 50s.

[0050] S4, determine that the third silicon nitride layer 4, the second silicon nitride layer 5, the first silicon nitride layer 6, the second silicon nitride oxide layer 7, the first silicon nitride oxide layer 8, and the silicon oxide layer 9 are overall heated by 20°C based on the current process temperature, and the highest temperature among all temperature data is 515°C, which is within the range of 460-540°C, and the front film structure is obtained after the PECVD process;

[0051] During normal circulation, the back film structure is prepared according to the production line process, and the electrical performance data is tested after screen printing. The UV attenuation test is carried out simultaneously. The electrical performance parameters are on par with the production line, and the UV attenuation is 1.53% lower than that of the production line, with obvious improvement effect.

[0052] The method uses atomic layer deposition technology (ALD) and H2O as a precursor source for a two-stage reaction. The amount of water phase source in the first stage should be higher than that in the second stage, and the number of reaction cycles should be higher than that in the second stage, so as to obtain a laminated aluminum oxide film 2 with a decreasing content of -OH groups; then a layer of silicon oxynitride film 3 is added on the front laminated aluminum oxide film 2 by plasma enhanced chemical vapor deposition (PECVD), and then a passivation film layer such as silicon nitride and silicon oxynitride is grown; at the same time, the laminated aluminum oxide film 2 with different reaction cycle numbers is matched with the silicon oxynitride film 3 with different reaction times, and the overall matching gradient temperature is synchronously increased. The stacked structure can greatly reduce the interface state density of aluminum oxide and protect the passivation film layer; at the same time, the addition of the silicon oxynitride film layer and the temperature increase process improves the film's ability to block H ions after UV irradiation, promotes the crystallization of the aluminum oxide film layer, and increases its effective thickness, thereby improving its chemical passivation and field passivation effects, thereby reducing the UV attenuation effect of the TOPCon battery, improving the reliability measures against UV attenuation, and compensating for the high efficiency loss of a single process of increasing the ALD reaction cycle.

[0053] The present invention takes into account the particularity of UV attenuation of N-type TOPCon batteries, improves the suitable laminated aluminum oxide film layer 2, avoids the defects of a single improvement method, and unifies the adaptation standards of the three variables of laminated aluminum oxide, newly added silicon oxynitride film 3, and overall temperature rise of the passivation film layer. The film layer structure design method can be adapted to actual usage conditions, and while improving the anti-UV attenuation effect, it can also ensure the high efficiency of the battery cell.

[0054] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0055] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a TOPCon battery front film layer with anti-UV attenuation effect, characterized in that: The following steps are involved: S1. Determine the total number of atomic layer deposition cycles and divide it into two parts: lower layer / upper layer, and the number of cycles of the lower layer is higher than that of the upper layer; S2. Based on the number of reaction cycles in S1, the content of the aqueous phase precursor source in the lower aluminum oxide film layer is ensured to be higher than that in the upper aluminum oxide film layer, different atomic layer deposition chamber reaction temperatures are set, and a stacked aluminum oxide film layer with a decreasing -OH group content is obtained by atomic layer deposition; S3, based on the total number of cycles in S1, determining whether the total number of cycles is high or low, and growing a high-thickness or low-thickness silicon oxynitride film according to the total number of cycles; S4. Based on S3, a passivation film layer is grown by matching the temperature rise amplitude with a low total number of cycles and a high thickness silicon oxynitride film or a high total number of cycles and a low thickness silicon oxynitride film.

2. The method for preparing a TOPCon battery front film layer with anti-UV attenuation effect according to claim 1, characterized in that: A TOPCon cell front film layer with anti-UV attenuation effect prepared by a method for preparing a TOPCon cell front film layer with anti-UV attenuation effect, wherein the front film layer structure comprises, from bottom to top, a laminated aluminum oxide film layer, a silicon oxynitride film grown on the laminated aluminum oxide film layer, and a passivation film layer; The stacked aluminum oxide film layer comprises an upper aluminum oxide film layer and a lower aluminum oxide film layer, and the -OH group content decreases from the lower aluminum oxide film layer to the upper aluminum oxide film layer.

3. The method for preparing a TOPCon battery front film layer with anti-UV attenuation effect according to claim 2, characterized in that: The total thickness of the laminated aluminum oxide film is 4.5±1.5 nm.

4. The method for preparing a TOPCon battery front film layer with anti-UV attenuation effect according to claim 2, characterized in that: The passivation film layer structure is respectively a third silicon nitride layer, a second silicon nitride layer, a first silicon nitride layer, a second silicon oxynitride layer, a first silicon oxynitride layer, and a silicon oxide layer from bottom to top.

5. The method for preparing a TOPCon battery front film layer with anti-UV attenuation effect according to claim 1, characterized in that: The water-phase precursor in S2 is introduced for 4-10 seconds at a flow rate of 2500-3500 sccm.

6. The method for preparing a TOPCon battery front film layer with anti-UV attenuation effect according to claim 5, characterized in that: In S2, during the preparation of the laminated aluminum oxide film, TMA is introduced using N2 as a source, with a flow rate of 2000-4000sccm and an introduction time of 6-8s.

7. The method for preparing a TOPCon battery front film layer with anti-UV attenuation effect according to claim 6, characterized in that: In S2, when preparing the lower aluminum oxide film layer, the reaction temperature of the atomic layer deposition chamber is 240-260°C, and when preparing the upper aluminum oxide film layer, the reaction temperature of the atomic layer deposition chamber is 265-275°C.

8. The method for preparing a TOPCon battery front film layer with anti-UV attenuation effect according to claim 7, characterized in that: The total thickness of the laminated aluminum oxide film obtained in S2 is 4.5±1.5 nm, and the high and low cycle numbers are divided according to the measured thickness as follows: 3.0nm≤low cycle number<3.5nm, 3.5nm≤medium cycle number<4.5nm, 4.5nm≤high cycle number.

9. The method for preparing a TOPCon battery front film layer with anti-UV attenuation effect according to claim 1, characterized in that: In S3, the process time for growing the silicon oxynitride film is 30-70 seconds.

10. The method for preparing a TOPCon battery front film layer with anti-UV attenuation effect according to claim 1, characterized in that: The temperature rise range in S4 is 10-30°C, and the total temperature range after the temperature rise is 460-540°C.

Citation Information

Patent Citations

  • Aluminum oxide film as well as preparation method and application thereof

    CN109457235A

  • Laminated passivation structure of TOPCon battery and TOPCon battery

    CN114497237A

Cited By

  • Ultraviolet attenuation resistant TOPCon battery and preparation method thereof

    CN120826076A

  • Anti-UVID anti-reflection passivation film and preparation method thereof

    CN121793516A